PERAN LEMBAGA SOSIAL TERHADAP PEMBINAAN MORAL REMAJA DI KELURAHAN BANUARAN NAN XX - Yohanis (Jurnal Administrasi Publik dan Pemerintahan, 2023)
The purpose of this study is to explain and describe the Role of Social Institutions towards Adolescent Moral Development in Banuaran Nan XX Village, Lubuk Begalung District, Padang City. The research method is descriptive qualitative of the research subject, namely Social Institutions which include Family Institutions, Educational Institutions, Religious Institutions, and Legal Institutions. Data collection techniques use interviews, observations and documentation while data analysis uses credibility and triangulation tests. The results of this study: there are adolescents who have poor morals, with the fact that there is juvenile delinquency